FIGURATIVE LANGUAGE IN THE SELECTED SONGS IN THE ALBUM “ONLY HUMAN” BY CALUM SCOTT - Tiara, Tiara; Weda, Sukardi; Burhamzah, Muftihaturrahmah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to suppress the answers to the research questions. The objective of this study are: (1) To find out the type of figurative language used in the lyrics of Calum Scott songs. (2) To identify the meaning of the figurative language used in the lyrics of Calum Scott selected songs. This research using a qualitative descriptive. The data sources of this research are several Calum Scott song lyrics contained in the album “ Only Human”, namely "You Are the Reason", "Only You", "What I Miss Most", "Dancing on My Own" and "Won't Let You Down". In this study the writers used the theory of Geoffrey N. Leech (1969). From the analysis, the results of this study showed that the total number of types of language styles used in Calum Scott song were 14 data. Based on the analysis of the meaning of figurative language, it can be seen that the meaning mostly describes the feelings of the singer implied by the figurative language used in the lyrics. It can be concluded that the role of using figurative language is important in the creation of song lyrics, because this type of language is used to create a meaningful sentence to give a certain effect by expressing feelings and ideas in such a way as to make the reader more impressed and the delivery of the message can be reflected well into the mind of the reader or listener.Keywords: Figurative Language, Meanings, Song Lyrics, Calum Scott.